Conference preferences and environmental sensitivity: Insights from participants to an Italian conference about planetary health - Fortunato, Corinna; Marjin, Corina; Briganti , Giovanni Leonardo; Gallinoro , Veronica; Raso, Eleonora; Traglia, Francesco; Grieco, Vittorio; Minutolo, Giuseppa (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background Scientific conferences may substantially contribute to greenhouse gas emissions, yet they remain essential for professional development. Understanding how health professionals perceive environmentally sustainable conference practices is key to designing low-impact scientific events. This study explored knowledge, attitudes, behaviors, and preferences regarding sustainable conference participation among attendees of an Italian planetary health meeting. Methods We administered an online survey to participants of the 2024 Public Health Residents’ Meeting “From Planet Earth to Planet Health” held in Ancona, Italy. The questionnaire assessed self-perceived environmental awareness, lifestyle behaviors, travel patterns, and preferences toward virtual, hybrid, and in-person conference formats. We evaluated associations between awareness and demographic or behavioral variables. Results Of 80 invited participants, 47 completed the survey. Most respondents were public health residents (70.2%) with balanced gender distribution. Environmental awareness was generally high but showed little association with demographic characteristics or lifestyle behaviors. A majority preferred in-person conferences (61.7%), perceiving them as superior for learning (68.1%) and especially for networking (87.2%). Virtual conferences were acknowledged for advantages such as lower cost, greater accessibility, and reduced environmental impact. However, environmental considerations minimally influenced conference participation decisions: only 25.5% reported considering them moderately or strongly, and just 12.8% had ever chosen a virtual format primarily for environmental reasons. Discussion In this exploratory study, despite high environmental awareness, limited associations were found between awareness with pro-environmental behaviors among conference participants, suggesting the complexity of sustainable decision-making in academic contexts. While participants recognized the ecological benefits of virtual formats, social and educational opportunities strongly anchored preferences toward in-person events. These insights suggest the potential value of institutional strategies, such as high-quality hybrid models and structured sustainability frameworks, to align scientific conferencing with environmental goals. Larger, multi-institutional studies are needed to validate these relationships and assess the feasibility of proposed strategies.